Assessment of virtual thermal manikins for thermal comfort numerical studies. Verification and validation. (2nd January 2022) - Croitoru, Cristiana; Nastase, Ilinca; Bode, Florin; Sandu, Mihnea
Abstract : In turbulent flows as in HVAC applications, the fluctuation of air speed can affect the sensation of thermal comfort. This study is a part of a larger experimental and numerical campaign intended to evaluate the influence of the turbulence intensity at the inlet of air distribution systems on the local draft sensation and thermal discomfort for different ventilation cases using numerical simulations. For five different imposed values of turbulence intensity (0%, 3%, 10%, 30%, 50%) the local heat loss for different body parts was quantified CFD simulations were performed using a realistic model of human body along with an experimental validation with a humanoid thermal manikin. The CFD model was further exploited for several cases to evaluate the influence of turbulence intensity on the comfort indicators and local heat loss. The recorded velocity, turbulence and temperature fields allowed us to estimate the distributions of DR, PPD and PMV indexes which showed no significant changes, but correlations were found for the imposed turbulence intensity and local heat loss on different body parts, indicating the influence on thermal perception.